ASSESSMENT OF VANCOMYCIN CONCENTRATIONS IN SYRINGES PREPARED WITHIN A WARD SETTING. Issue 9 (17th August 2016) - Saimbi, Sarina; Batchelor, Hannah; Whitticase, Louise; Holder, Gemma; Russell, Alison Bedford
Abstract : Aim: Vancomycin is used as a second line antibiotic in the treatment of late onset neonatal infection for its activity against coagulase negative staphylococci. Vancomycin infusions are prepared within a ward setting for administration to neonates. Differences in preparation techniques on the ward have previously been recognised as a potential source of variation in vancomycin concentrations, as compared to concentrations in pre-made preparations. This study analyses a consecutive series of vancomycin syringes prepared in a ward for administration to neonates, to determine how accurate the concentration of each preparation was compared to the expected concentration. Method: Vancomycin concentrations were determined by UV analysis (λ=280 nm) with a UV spectrophotometer (Jenway Genova Plus). A calibration curve for vancomycin was created (R2=0.9996) by manufacturing a series of solutions of vancomycin hydrochloride in glucose 5% w/v. Samples of vancomycin from syringes from which doses were administered to neonates were then analysed to assess their concentration. For each syringe, mean vancomycin concentration±standard deviation was calculated (n=3). Reasonable errors in preparations were calculated based on errors in each step of the preparation process. Theoretical error was calculated based on apparatus used, and experimental error was recorded based on a simulated process. Two preparation methods were compared; the method complying with that described in the local formulary, 1 and an alternative method reported by the nurses preparing the dose. Results: Analysis of results showed that concentration of the vancomycin syringes prepared ranged from 0.85 to 8.24 mg/mL. The expected concentration was 4.17 mg/ml. Theoretical error in preparation of vancomycin doses was lower with the formulary-compliant method1 versus an alternative method, as were variations in in vancomycin concentration. Depending on the type of error (theoretical or experimental) and method by which vancomycin syringes were prepared (formulary1 or alternative method), the percentage of syringes with vancomycin concentration outside of the specified ranges varied from 20%–43%. This is higher compared to the findings of the Department of Health2, where it was found that 19.2% of morphine infusions prepared by nurses in the neonatal intensive care unit were outside British Pharmacopoeia concentration limits. Conclusion: Preparation of vancomycin doses should follow the formulary method1 to minimise variation in concentration of the final product. Alternatively, pre-made syringes may be preferred as an alternative to ward-made syringes as this removes individualised preparation as a source of error.